Prospective study of post-transfusion hepatitis after cardiac surgery in a British centre. Issue 6403 (12th November 1983) - Collins, J D; Bassendine, M F; Codd, A A; Collins, A; Ferner, R E; James, O F
Abstract : A series of 248 consecutive patients undergoing cardiac surgery were examined in a prospective study of post-transfusion hepatitis in a single British centre. Patients received a total of 1796 units of blood or blood products (mean blood transfusion 6.28 units per patient). During five to 30 days after operation 38 of the patients showed an increase in serum transaminase activities. There was no serological evidence for fresh infection by hepatitis A or B virus, cytomegalovirus, Epstein-Barr virus, or herpes virus in any of these patients. The increase in transaminase activities was unexplained and reached over 100 IU/l (normal less than 40 IU/l) in six patients. The incidence of acute short incubation post-transfusion non-A, non-B hepatitis was therefore thought to be 2.4%. These six patients had normal liver function six months after transfusion but a further two of the surviving 228 patients had raised serum transaminase activities at six months. In one of these, liver biopsy disclosed chronic persistent hepatitis; in the other, alcoholic liver disease was suspected. The incidence of significant chronic liver disease after blood transfusion possibly attributable to a non-A, non-B hepatitis agent was therefore only 0.4%.